Analisis Keberlanjutan Usahatani Sawah Bukaan Baru di Kabupaten Bangka - Feriadi; Dwi Sadono; Ninuk Purnaningsih (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2023)
New rice fields are one of the solutions to increase food availability in Bangka Regency. This study aims to analyze the effect of individual characteristics, characteristics of innovation, external support, and motivation on the sustainability of new open rice farming. This research was conducted by in-depth interviews with 121 respondents of newly opened rice fields in Kemuja and Balunijuk villages in March – June 2022. The number of research samples was determined by the simple cluster sampling method. The research instrument used was a questionnaire with direct interviews with respondent farmers. Data were analyzed using Partial Least Square (PLS)-SEM analysis. The results showed that the sustainability of farming in farming profits was in a low category, while the aspects of production and marketing were in the medium category. Base on result of the SmartPLS-SEM test, it is known that the sustainability of farming in newly opened rice fields is influenced by external support, innovation characteristics and motivation factors.